Development of QR Code-Based Booklet to Prevent Inhalant Abuse of Elementary School Students in Palopo City - Sabani, Fatmaridah; Bulu, Rifaah Mahmudah (Mimbar Sekolah Dasar, 2024)
This research is motivated by the many cases of narcotics abuse in Indonesia which have now been found in various regions including the city of Palopo. This study aims to educate the public from an early age about the dangers of narcotics and hazardous substances such as inhalant abuse as a preventive measure for the development of narcotics cases in Indonesia, especially in Palopo City. This research uses the RD method by developing a QR Code-based booklet as educational media for elementary school students and teachers. The results of this study found that the QR Code-based booklet product to prevent inhalant abuse behavior in elementary school students was declared valid or feasible to use. Furthermore, the teacher's response in the practicality test of the QR Code-based booklet to prevent inhalant abuse behavior was declared practical to use. In this study, it was also found that there was an increase in learning outcomes before and after the application of QR Code-based booklets to prevent inhalant abuse behavior.